2022
DOI: 10.1159/000526379
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Recommendations and Practices in School Feeding: A Systematic Review

Abstract: Considering the importance of schools for sustainable food offers and the formation of conscientious citizens on sustainability, this systematic review aimed to verify the recommendations on sus­tainability in school feeding policies and the sustainability practices adopted in schools. The research question that guided this study is “what are the recommendations on sustainability in school feeding policies and the sustainability practices adopted in schools?”. This systematic review was prepared according to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…A systematic review verified the recommendations on sustainability in school feeding policies and practices adopted in schools and found that recommendations for purchasing sustainable food (organic, local and seasonal), nutrition education focused on sustainability and food waste reduction were frequent (23) . The relationship between sustainability and the SFP also occurs at the decision level at all stages of meal production, including menus.…”
Section: School Feeding Programme Promotes Sustainable Feeding and Fo...mentioning
confidence: 93%
See 1 more Smart Citation
“…A systematic review verified the recommendations on sustainability in school feeding policies and practices adopted in schools and found that recommendations for purchasing sustainable food (organic, local and seasonal), nutrition education focused on sustainability and food waste reduction were frequent (23) . The relationship between sustainability and the SFP also occurs at the decision level at all stages of meal production, including menus.…”
Section: School Feeding Programme Promotes Sustainable Feeding and Fo...mentioning
confidence: 93%
“…Thus, sustainable SFP development is possible, regardless of the size of the state or country. The mandatory purchase of family farming or a popular and solidarity economy through laws is a strategy that not only supports family farming by connecting farmers with a secured market with pre-negotiated prices but also increases the amount of local and fresh products available in school menus (23) . Different Latin American countries, such as Ecuador, Guatemala and Honduras, have included the obligation to buy food locally in their SFP, encouraging family farmers and the poor and vulnerable sectors of the population (24) .…”
Section: School Feeding Programme Promotes Sustainable Feeding and Fo...mentioning
confidence: 99%